Effect of Zidovudine on the Primary Cytolytic T-Lymphocyte Response and T-Cell Effector Function - Francke, Sabine (American Society for Microbiology, 2000)
Azidothymidine (AZT) and other nucleoside analogues, used to treat AIDS, can cause severe clinical side effects and are suspected of suppressing immune cell proliferation and effector immune cell function. The purpose of the present study was to quantitatively measure the effects of AZT on cytotoxic T-lymphocyte (CTL) priming and to determine if the major histocompatibility complex-restricted CTL killing was affected by AZT exposure. For this purpose, we employed a murine alloantigen model and limiting-dilution analysis (LDA) to estimate cytotoxic effector cell frequencies of alloreactive splenocytes treated with drug during antigen sensitization. This noninfectious model was chosen to avoid analysis of a virus-compromised immune system. Exposure of splenocytes to therapeutic concentrations of AZT (2 to 10 μM) caused a two- to threefold dose-dependent reduction in CLT precursor frequency. This reduction was caused by decreased proliferation of alloantigen-specific CTLs rather than loss of function, because full cytolytic function could be restored by adjusting the AZT-treated effector/target cell ratios to that of untreated cells. In addition, when AZT was added to the assay system at various times during antigen sensitization there was a time-related loss of the suppressive effect on the generation of cytolytic effector function, suggesting that functional CTLs are not affected by even high doses of AZT. Taken together, the data indicate that the reduction of CTL function associated with AZT treatment is due to a quantitative decrease of effector cell precursor frequency rather than to direct drug cytotoxicity or interference with mediation of cytolysis. Furthermore, antigen-naive immune cells were most sensitive to this effect during the first few days following antigen encounter.